2017
DOI: 10.1016/j.jaad.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of and risk factors for tumor upstaging after wide local excision of primary cutaneous melanoma

Abstract: Clinicopathologic characteristics, particularly anatomic location on the head, neck, hands, feet, genitals, or pretibial leg and subtotal diagnostic biopsies, identify melanomas with an increased risk for upstaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 47 publications
0
39
0
Order By: Relevance
“…Among SLNB‐eligible patients, 4 of the unsuccessful SLNBs occurred in patients who underwent SLNB after surgical resection with MMS‐IHC. Head and neck location is a risk factor for upstaging of melanoma during excision 63 . Although studies have shown that SLNB can be performed with accuracy after excision of the primary melanoma, 4,64,65 thorough tumor sampling is recommended for accurate staging before the excision of head and neck melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…Among SLNB‐eligible patients, 4 of the unsuccessful SLNBs occurred in patients who underwent SLNB after surgical resection with MMS‐IHC. Head and neck location is a risk factor for upstaging of melanoma during excision 63 . Although studies have shown that SLNB can be performed with accuracy after excision of the primary melanoma, 4,64,65 thorough tumor sampling is recommended for accurate staging before the excision of head and neck melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…3 The need to return to the operating room for SLNB when T-upstaging resulted is slightly higher in the head and neck than in other regions of the body and is very possibly due to the higher incidence of T-upstaging in cutaneous melanoma of the head and neck versus other body regions. 11…”
Section: Discussionmentioning
confidence: 99%
“…These data provide insight into recent studies that found that cutaneous melanoma of the head and neck is more likely to be upstaged and more likely to have positive margins on the DWLE specimen when compared with cutaneous melanoma of other regions of the body. 11,13…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations